Rancang Bangun Platfrom Freelance Digital Berbasis Web Menggunakan Metode Waterfall - Muhammad Alvin Azzamul Azmi; Irwan Alnaurus Kautsar; Nuril Lutvi Azizah; Novia Ariyanti (LPPM UBHINUS MALANG, 2024)
With advances in technology, people can now work independently without having to come to work. This is thanks to technology which is increasingly widespread in various aspects of human life. Especially among the younger generation, interest in becoming freelancers is increasing because of the flexibility of work schedules that allow them to work from anywhere. Apart from that, they can collaborate with clients from various countries via the internet. In this research, the author uses the waterfall development method, which emphasizes structured steps starting from identifying needs to system maintenance. In conclusion, this program has succeeded in facilitating collaboration between freelancers who need work partners on agreed projects. My freelance platform allows anyone to register as a freelancer and partner, making it easier for them to find work. The program testing results show a success percentage of 93%.